Statistical survey on inspection, diagnosis and repair of wall renderings - Sá, Gonçalo; Sá, João; Brito, Jorge de; Amaro, Bárbara (Journal of Civil Engineering and Management, 2015)
This paper describes a statistical survey on the pathology, diagnosis and rehabilitation of wall renderings. The survey was based on an inspection and diagnosis support system that comprises the classification of anomalies in renderings, their most probable causes, diagnosis methods and repair and maintenance techniques. The on-site work that led to this statistics collection involved standard inspections of 55 buildings, located in Lisbon, and a total of 150 wall renderings (100 external and 50 interior). The results of this survey provide indications on the intervention actions at the design, execution and use/maintenance stages in order to decrease the magnitude of or eradicate anomalies in wall renderings. The implementation of a system of this kind could directly improve the quality of constructions.